Effects of the oil spill at the La Pampilla Refinery on the seacoast of Lima (Peru) - Pulido Capurro, Victor (2022)
The oil spill that occurred on the sea coast of the La Pampilla Refinery has caused an environmental disaster of incalculable dimensions. Reports indicate that the product of the spill is 11,900 barrels of oil and the spread of crude oil is 1,739,000 square meters, which includes 24 contaminated beaches and 116 square kilometers impacted by the oil, between sea and land. The spilled oil has been displaced by marine currents in a northerly direction, affecting the habitats and biodiversity of the 512 hectares of the Reserva Nacional Sistema de Islas, Islotes y Puntas Guaneras and the 1758.1 hectares of the Zona Reservada Ancón. Nearly 500 species of invertebrates, marine algae, birds and mammals have been directly affected and, likely, they will not return to the habitats where they resided before the spill and which have been destroyed by the contamination. The objective of the editorial is to describe the possible environmental effects of the oil spill, which in itself contravenes the "human-environment interaction", while providing inputs for academic debate so that scientists can propose remediation strategies for the environmental disaster that has occurred in favor of biodiversity conservation and sustainability. The Revista de Investigaciones Altoandinas is always attentive to everything that may be harmful to the environment and human health, especially to induce the balance of "interaction between human beings and the environment", from different disciplines and institutions of knowledge.